Microalgae based wastewater treatment for the removal of emerging contaminants: A review of challenges and opportunities - Maryjoseph, S.; Ketheesan, B. (Elsevier, 2020)
Emerging contaminants (ECs) are attracting considerable attention due to their potential risk to human health and ecosystem. The past decade has seen a renewed importance in microalgae for bioremediating ECs from wastewater. Several proof of concept studies have been published to rationalize the use of microalgae for bioremediating ECs at laboratory conditions. However, there has been little discussion on real world application of microalgae for bioremediation purposes. This review paper sheds new light on obstacles faced in commercial use of microalgae for bioremediating ECs. The presence of multiple ECs and their affinity for microalgae raise some concern about the validity of laboratory findings. Dynamic changes of environmental conditions and accidental contaminations can significantly influence rate of bioremediation in large scale system. Appropriate pilot scale studies may bridge the gap between the laboratory scale studies and commercial scale applications. Considering the fate of ECs in microalgal cell, more research is needed in the direction of biodegradation assisted bioremediation due to end use of algal biomass. In fact, a wide range of extremophile microalgae species can be screened for selective removal of ECs. In-depth investigations are needed to characterize the quality of wastewater effluent after the separation of microalgal biomass. Notably, life cycle analysis related studies are needed to look at the viability of microalgae assisted bioremediation of ECs.